BC-TFdb: a database of transcription factor drivers in breast cancer. (21st April 2021) - Khan, Abbas; Khan, Taimoor; Nasir, Syed Nouman; Ali, Syed Shujait; Suleman, Muhammad; Rizwan, Muhammad; Waseem, Muhammad; Ali, Shahid; Zhao, Xia; Wei, Dong-Qing
Abstract: Transcription factors (TFs) are DNA-binding proteins, which regulate many essential biological functions. In several cancer types, TF function is altered by various direct mechanisms, including gene amplification or deletion, point mutations, chromosomal translocations, expression alterations, as well as indirectly by non-coding DNA mutations influencing the binding of the TF. TFs are also actively involved in breast cancer (BC) initiation and progression. Herein, we have developed an open-access database, BC-TFdb (Breast Cancer Transcription Factors database), of curated, non-redundant TF involved in BC. The database provides BC driver TFs related information including genomic sequences, proteomic sequences, structural data, pathway information, mutations information, DNA binding residues, survival and therapeutic resources. The database will be a useful platform for researchers to obtain BC-related TF–specific information. High-quality datasets are downloadable for users to evaluate and develop computational methods for drug designing against BC. Database URL : https://www.dqweilab-sjtu.com/index.php .